PENGARUHBULLYING DI TEMPAT KERJA TERHADAP KEINGINAN KELUAR: EFEK MEDIASI KOMITMEN ORGANISASIONAL AFEKTIF - Djamilah, Siti; Julindrastuti, Dijah; Karyadi, Iman (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2012)
This study examined the effect of affective organizational commitment as a mediating variable of workplace bullying and intention to leave. This study tested tothe company's employees in Surabaya, Sidoarjo, Gresik and Mojokerto. Questionnaires were distributed to 120 respondents and was completed by 111 respondents. The next step, researchers examined the validity and reliability of variables: affective organizational commitment, workplace bullying and intention to leave. All the variables have good validity and reliability. Hierarchical regression was used to examine the effects of affective organizational commitment as a mediating variable of workplace bullying and intention to leave. Hierarchical regression results indicate that the effect of affective organizational commitment as a mediating variable of workplace bullying and intention to leave was rejected. Affective organizational commitment better as the independent variable of intention to leave. Thus, the intention to leave is influenced by affective organizational commitment and workplace bullying.